Anterior repositioning splint treatment consideration for cases of disc displacement with reduction - Tjang, Steven Alexander; Tanti, Ira (Indonesian Journal of Prosthodontic, 2020)
The focus of this literature review is to explore the process of disc displacement with reduction (DDWR) and how the treatment using anterior repositioning splint (ARS) can positively affect patients who are diagnosed with DDWR. The use of MRI as the gold standard of TMJ study allows current researcher to re-consider the common theory whereby DDWR ultimately progresses into disc displacement without reduction or other advanced internal derange-ment process. The use of ARS can produce resolution of pain in patients who are experiencing DDWR with joint pain. However, the use of ARS is shown to be effective on short term only, and its use must be accompanied by other modalities such as physical self-regulation (PSR). The lack of gold standard for the treatment of DDWR prompts healthcare worker to provide patients with conservative treatment before offering more advanced and sur-gical procedure, both of which carries additional unwanted risk. Overall, the use of ARS is shown to be very effective and non-invasive.